2016
DOI: 10.1007/s10311-016-0589-8
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution below WHO levels decreases by 40 % the links of terrestrial microbial networks

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…Overall, perturbed systems show lower connections (edges) than no-perturbed systems. For example, urban air (polluted) showed 40% fewer connections than rural air (no polluted) (Karimi et al, 2016). This pattern has also been observed in soil systems by different land uses, where crop soils have shown lower connections than natural forest soils (Lupatini et al, 2014).…”
Section: Discussionmentioning
confidence: 62%
“…Overall, perturbed systems show lower connections (edges) than no-perturbed systems. For example, urban air (polluted) showed 40% fewer connections than rural air (no polluted) (Karimi et al, 2016). This pattern has also been observed in soil systems by different land uses, where crop soils have shown lower connections than natural forest soils (Lupatini et al, 2014).…”
Section: Discussionmentioning
confidence: 62%
“…Instead of biodiversity, non-random patterns in microbial species co-occurrence and associated metrics are being integrated to amplify the differences that subtle perturbation make [20,51], e.g. a temperature increase of 1 °C for 5 years [19], soil contamination with mercury for several decades [16], and annual litter decomposition [17]. Our analysis provides a framework for studying microbial communities, co-occurrence, and networks under mild anthropogenic perturbation by adding S. acidaminiphila.…”
Section: Discussionmentioning
confidence: 99%
“…This whole new way of artificially disturbing a microbial ecosystem at a small scale provides a chance for researchers to observe and investigate changes in microbial communities in response to gradual and subtle perturbation. In addition, the generalization of such laboratory-scale experimental findings to real environmental changes might help monitor and sound the alarm about mild changes from chronic atmospheric pollution [19], agricultural practices [17], and metallic contaminants in the soil [16] at an early stage, which can then be countered with ecosystem management strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another set of community-wide metrics can be computed from the structure of biotic interactions within ecological networks (reviewed in Vacher et al, 2016;Layeghifard et al, 2017). Based on empirical evidence of the variation in network structure under environmental disturbance (Tylianakis et al, 2007;Zhou et al, 2011;Karimi et al, 2016;Ma et al, 2018), their properties have been suggested as potential indicators of ecosystem functioning and integrity (Gray et al, 2014;Karimi et al, 2017;Bohan et al, 2011Bohan et al, , 2017Lau et al, 2017;Tylianakis et al, 2017;Pellissier et al, 2018;Delmas et al, 2019). In recent years, a growing interest in these approaches has led to a series of studies employing EG to infer ecological networks from microbial communities data (Zhou et al, 2011;Lupatini et al, 2014;Zappelini et al, 2015;Pérez-Valera et al, 2017;Pauvert et al, 2019) and from macroinvertebrates (Compson et al, 2019) to explore the links between network properties (e.g.…”
Section: The Environmental Genomics Revolution For Biodiversity Reseamentioning
confidence: 99%